2021
DOI: 10.1248/cpb.c20-00745
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Stereochemistry of Amphidinolide N Congeners from Marine Dinoflagellate <i>Amphidinium</i> Species

Abstract: Two highly potent cytotoxic 26-membered macrolides, isocaribenolide-I (1) and a chlorohydrin 2, together with known amphidinolide N (3), have been isolated from a free-swimming dinoflagellate Amphidinium species (KCA09053 and KCA09056 strains) collected off Iriomote Island, Japan. The structures of 1 and 2 were determined to be a congener of 3 with an isobutyl terminus and the chlorohydrin form of 3, respectively, by detailed analyses of spectroscopic data. The relative stereochemistries of 1 and 2 were elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…disclosed their synthesis of 232 , Tsuda and coworkers published a new proposed structure for amphidinolide N on the basis of extensive NMR studies on both amphidinolide N itself and two closely related analogs (Scheme 39). [168] Interestingly, this new structure ( 233 ) is the C2,C10,C14,C15‐tetraepimer of the revised structure that Kobayashi disclosed in 2013 ( 208 ), [153] and exhibits the same configuration at C15 as des ‐epoxyamphidinolide N ( 232 ). Assuming that the overall conformation of these molecules is indeed critical for epoxidation as Trost proposed, the stereochemical differences between 208 , 232 , and 233 are notable, and may help explain why 232 was difficult to epoxidize.…”
Section: (−)‐Des‐epoxyamphidinolide Nmentioning
confidence: 91%
“…disclosed their synthesis of 232 , Tsuda and coworkers published a new proposed structure for amphidinolide N on the basis of extensive NMR studies on both amphidinolide N itself and two closely related analogs (Scheme 39). [168] Interestingly, this new structure ( 233 ) is the C2,C10,C14,C15‐tetraepimer of the revised structure that Kobayashi disclosed in 2013 ( 208 ), [153] and exhibits the same configuration at C15 as des ‐epoxyamphidinolide N ( 232 ). Assuming that the overall conformation of these molecules is indeed critical for epoxidation as Trost proposed, the stereochemical differences between 208 , 232 , and 233 are notable, and may help explain why 232 was difficult to epoxidize.…”
Section: (−)‐Des‐epoxyamphidinolide Nmentioning
confidence: 91%
“…335 Two new amphidinolide N congeners 874 and 875 are potent cytotoxins isolated from Amphidinium sp. 336 A report of three new amphidiniols 876–878 has suggested that centrifugation to clarify the culture media is a stressor that prompts release of the compounds from the dinoflagellate into the surrounding liquid. 337 Karenia brevisulcata is a well-documented producer of potently toxic metabolites, with two new brevisulcenal-type sulfated esters 879 and 880 being sourced from a New Zealand isolate of the dinoflagellate.…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…The most potent anticancer compounds identified to date are two macrolides (isocaribenolide-I and chlorohydrin-2) recently isolated from a free-living Amphidinium sp. (strain KCA09053) and found to possess high cytotoxic activity against human cervix adenocarcinoma cells [68]. Caribenolide I, isolated from a free-living Amphidinium sp., was found to possess cytotoxic activities towards human colon tumour cells [69].…”
Section: Anticancer Activitymentioning
confidence: 99%